A non-land policy for global sustainable land use? - Kaphengst, Timo; Wolff, Franziska; Wunder, Stephanie (Ökologisches Wirtschaften - Fachzeitschrift, 2015)
What are new ways and future options for the international governance of sustainable land use? Effective policies towards more sustainable land use should not only deal with land and soil. These policies need to address various drivers and different contexts in an integrated manner.